2017
DOI: 10.1002/acm2.12163
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to passive electron intensity modulation

Abstract: This work introduces a new technology for electron intensity modulation, which uses small area island blocks within the collimating aperture and small area island apertures in the collimating insert. Due to multiple Coulomb scattering, electrons contribute dose under island blocks and lateral to island apertures. By selecting appropriate lateral positions and diameters of a set of island blocks and island apertures, e.g. a hexagonal grid with variable diameter circular island blocks, intensity modulated beams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Island blocks were placed on a 0.6‐cm hexagonal grid (specified at 93.5 cm source to collimator distance). For each grid point on the hexagonal grid the algorithm first calculated the island block diameter d based on fraction of area blocked using 15 dr,0.166667emIRF=r23π)(1IRF1-0.166667em2,where r is the distance separating the hexagonally packed circular island blocks of diameter d , and italicIRF is the intensity reduction factor, which equals the ratio of the desired underlying intensity to that in the absence of the intensity modulator, that is, )(wi,j. Then, the algorithm selected an island block diameter closest from a set of available tungsten island block diameters ( cf .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Island blocks were placed on a 0.6‐cm hexagonal grid (specified at 93.5 cm source to collimator distance). For each grid point on the hexagonal grid the algorithm first calculated the island block diameter d based on fraction of area blocked using 15 dr,0.166667emIRF=r23π)(1IRF1-0.166667em2,where r is the distance separating the hexagonally packed circular island blocks of diameter d , and italicIRF is the intensity reduction factor, which equals the ratio of the desired underlying intensity to that in the absence of the intensity modulator, that is, )(wi,j. Then, the algorithm selected an island block diameter closest from a set of available tungsten island block diameters ( cf .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Hogstrom et al 15 developed a simple, potentially economical method for design and fabrication of a passive radiotherapy intensity modulator for electrons (PRIME) device, 16 analogous to the utilization of x‐ray compensators for IMXT prior to the widespread availability of x‐ray multi‐leaf collimators (MLCs). 17 , 18 The objective of this paper is to describe a process that should be suitable for planning and delivery of IM‐BECT.…”
Section: Introductionmentioning
confidence: 99%
“…As the HEE delivery machines currently deliver beam pulses every few milliseconds, and the pulses are typically on the order of one or more Gray-per-pulse, this would require a very fast moving MLC to achieve the desired field modulation and such a technology is not currently yet available [36]. Alternatively, there has been development of intensity modulated passive scattering applicator devices to achieve conformal and homogeneous dose, without compromising substantially maximum depths that can be treated [37,38]. Rahman et al [39] demonstrated the feasibility of plan and dose calculation with the use of this passive delivery method for an electron UHDR beam produced from a modified medical linac.…”
Section: Uhdr Hee Delivery Techniques and Challengesmentioning
confidence: 99%
“…Initially, delivery of intensity modulation was envisioned using eMLCs, such as those reported by Hogstrom et al 20 and Gauer et al 21 ; however, access to said devices by the typical clinic has not been forthcoming. As an alternative, Hogstrom et al 22 reported a passive method for electron intensity modulation, which consists of a matrix of variable small‐diameter, high‐density island blocks, as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…The fraction of area locally blocked, which controls the intensity reduction factor (IRF) locally, is governed by the ratio of block diameter (d) to hexagonal grid spacing (r), 22 IRF=1.0π23dr2.…”
Section: Introductionmentioning
confidence: 99%